FAKTOR-FAKTOR YANG MEMENGARUHI RETURN SAHAM - Johan, Johan; Suhendah, Rousilita; Daryatno, Andreas Bambang (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence on effects of covid-19, price volatility, and stocks liquidity on stocks return of index LQ45 companies listed on the Indonesian Stock Exchange during 2020 period with a sample of 45 companies after going through the method. purposive sampling. Data processing uses multiple regression analysis helped by Eviews 11 and Microsoft Excel 2016. The results of this study indicate that covid-19 has a significant negative effect on stocks return, while price volatility and stocks liquidity have significant positive effect on stocks return. The implication of this research is need to increase price volatility and stocks liquidity for company that will increase the stocks return which will bring a good signal for investors.